2017
DOI: 10.1021/jacs.7b08064
|View full text |Cite
|
Sign up to set email alerts
|

Remote Migratory Cross-Electrophile Coupling and Olefin Hydroarylation Reactions Enabled by in Situ Generation of NiH

Abstract: A highly efficient strategy for remote reductive cross-electrophile coupling has been developed through the ligand-controlled nickel migration/arylation. This general protocol allows the use of abundant and bench-stable alkyl bromides and aryl bromides for the synthesis of a wide range of structurally diverse 1,1-diarylalkanes in excellent yields and high regioselectivities under mild conditions. We also demonstrated that alkyl bromide could be replaced by the proposed olefin intermediate while using n-propyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(101 citation statements)
references
References 91 publications
4
93
2
1
Order By: Relevance
“…To support the chain‐walking proposal further, alkene ( R )‐ 1 s containing a pre‐existing stereogenic center in the alkyl chain was evaluated (Scheme f). Preservation of the chiral integrity was observed in this case which is also consistent with the non‐dissociated chain‐walking mechanism, in contrast to the partial racemization of this stereocenter under our previous reductive chain‐walking conditions …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…To support the chain‐walking proposal further, alkene ( R )‐ 1 s containing a pre‐existing stereogenic center in the alkyl chain was evaluated (Scheme f). Preservation of the chiral integrity was observed in this case which is also consistent with the non‐dissociated chain‐walking mechanism, in contrast to the partial racemization of this stereocenter under our previous reductive chain‐walking conditions …”
Section: Resultssupporting
confidence: 89%
“…Distinct from the previously reported nickel‐catalyzed reductive remote hydroarylation systems, two precedents of redox‐neutral olefin remote hydroarylation have been reported by Lee and by Hartwig . However, the scope of the arylation is limited to only trifluoromethylarenes or heteroarenes with low p K a values.…”
Section: Introductionmentioning
confidence: 90%
“…4f). H/D exchanges both in the double bond moiety (73% D) and benzylic position (15% D) revealed that iterative Ni-(H)D species addition/elimination steps existed during the reaction process 63,64 .…”
Section: Resultsmentioning
confidence: 99%
“…[13] As part of our ongoing interest in metal-catalyzed electrochemistry [14] and 1,1-diarylalkane synthesis, [15] we questioned whether electrochemical reductive relay crosscoupling of alkyl bromides and aryl bromides could take place by taking advantage of chain-walking of an alkyl-nickel species. [16][17][18][19] Herein, we report the first such example of Nicatalyzed electrochemical relay cross-coupling of aryl halides and alkyl bromides, affording 1,1-diarylalkanes with good to excellent selectivities and yields (Scheme 1 b). This envisioned transformation is challenging as a result of a multitude of undesired side reactions, including those depicted in paths a, b, and c (Scheme 1 c).…”
mentioning
confidence: 99%